Is the application of fish skin graft (FSG) a beneficial addendum to standard care in the healing process in patients with diabetic foot ulcers (DUFs)? A Systematic review ... - Καραφωτάκη, Κυριακή Φωτίου (Aristotle University of Thessaloniki, 2023)
Background: The main purpose of this systematic review is to evaluate the application of fish skin grafts as a beneficial addition to standard care in the healing process of patients with diabetic foot ulcers. Diabetes mellitus affects a large portion of the global population, and its complications cause significant morbidity and mortality among patients. Diabetes foot ulcers are a major complication, with roughly one-quarter of diabetic patients acquiring a foot ulcer at some point in their lives. Amputations due to DFU will occur in nearly half of patients, and within five years, 70% of those who have such an amputation will die. To address this condition, it is important to manage diabetes effectively and treat the wound properly. This may involve controlling blood sugar levels and using specialized wound care products. Fish skin graft originated from the Atlantic Cod, have an intact rich lipid profile in omega-3 fatty acids, collagen type 1, and other nutrients that support the healing process, functions ... : Ιστορικό: Ο κύριος σκοπός αυτής της συστηματικής ανασκόπησης είναι η αξιολόγηση της εφαρμογής μοσχευμάτων δέρματος ψαριού ως ευεργετική προσθήκη στη διαδικασία της επούλωσης, στην βασική φροντίδα ελκών διαβητικού ποδιού. Ο σακχαρώδης διαβήτης επηρεάζει μεγάλο μέρος του παγκόσμιου πληθυσμού και οι επιπλοκές του προκαλούν σημαντική νοσηρότητα και θνησιμότητα στους ασθενείς αυτούς. Τα διαβητικά έλκη ποδιού είναι μια σημαντική επιπλοκή, με περίπου το ένα τέταρτο των διαβητικών ασθενών να αποκτούν έλκος στα κάτω άκρα κάποια στιγμή στη ζωή τους. Ακρωτηριασμός λόγω διαβητικών ελκών θα συμβούν σχεδόν στους μισούς ασθενείς και μέσα σε πέντε χρόνια, το 70% όσων έχουν υποβληθεί σε τέτοια χειρουργική παρέμβαση, θα πεθάνουν. Για να αντιμετωπιστεί αυτή η κατάσταση, είναι σημαντική η σωστή διαχείριση του διαβήτη και της κατάλληλης θεραπείας του διαβητικού έλκους. Αυτό μπορεί να περιλαμβάνει τον αναγκαίο και εξατομικευμένο έλεγχο των επιπέδων σακχάρου στο αίμα και τη χρήση εξειδικευμένων προϊόντων περιποίησης τραυμάτων. Το ...